2005
DOI: 10.1021/jf0521698
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Cysteine, Tryptophan, and Methionine Residues in Continuous Phase β-Lactoglobulin in Oil-in-Water Emulsions

Abstract: Proteins dispersed in the continuous phase of oil-in-water emulsions are capable of inhibiting lipid oxidation reactions. The antioxidant activity of these proteins is thought to encompass both free radical scavenging by amino acid residues and chelation of prooxidative transition metals; however, the precise mechanism by which this occurs remains unclear. In this study, the oxidative stability of cysteine, tryptophan, and methionine residues in continuous phase beta-lactoglobulin (beta-Lg) in a Brij-stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(156 citation statements)
references
References 29 publications
(53 reference statements)
6
148
2
Order By: Relevance
“…Such specific cysteine localization could possibly indicate a role for disulfide bridge interactions by the middle region of the protein. Cysteine residues are also known for their potential roles as antioxidants owing to the hydrogen atom in the thiol group available for donation (Elias et al 2005). Yu et al (2011) demonstrated that cysteine containing byssal proteins in marine mussels can reduce oxidized DOPA (dopaquinone) back to DOPA, restoring adhesive function, and can later transform into a cross-linker forming S-cysteinyldopa adducts.…”
Section: Dpfp5mentioning
confidence: 99%
“…Such specific cysteine localization could possibly indicate a role for disulfide bridge interactions by the middle region of the protein. Cysteine residues are also known for their potential roles as antioxidants owing to the hydrogen atom in the thiol group available for donation (Elias et al 2005). Yu et al (2011) demonstrated that cysteine containing byssal proteins in marine mussels can reduce oxidized DOPA (dopaquinone) back to DOPA, restoring adhesive function, and can later transform into a cross-linker forming S-cysteinyldopa adducts.…”
Section: Dpfp5mentioning
confidence: 99%
“…Several studies have demonstrated that proteins dispersed in the continuous phase of oilin-water emulsions can inhibit deleterious oxidation reactions by a combination of metal chelation and free radical scavenging (Elias, McClements, & Decker, 2005;Elias, McClements, & Decker, 2007). Whey protein isolate (WPI) is a surface-active globular protein and can be adsorbed to oil droplet surfaces in the form of a monolayer.…”
mentioning
confidence: 99%
“…Similarly, depleted levels of cysteine also indicated a higher demand for this amino acid intracellularly in response to oxygen. Cysteine itself has strong antioxidant activity (32) and is a key precursor for glutathione and a key metabolite in the synthesis of other sulfur-containing compounds, including thiamine, coenzyme A (CoA), and biotin, which have all been implicated in the oxidative stress response in other organisms such as Escherichia coli and Bacillus subtilis (33,34).…”
Section: Resultsmentioning
confidence: 99%